Laparoscopic splenopancreatectomy for an endocrine tumor with cystic changes: a case report. Issue 3 (6th February 2017) - Izumi, Hideki; Yazawa, Naoki; Furukawa, Daisuke; Masuoka, Yoshihito; Yamada, Misuzu; Mashiko, Taro; Kawashima, Yohei; Ogawa, Masami; Kawaguchi, Yoshiaki; Mine, Tetsuya; Hirabayashi, Kenichi; Nakagohri, Toshio
Key Clinical Message: The biological behavior of a cystic pancreatic endocrine neoplasm is less aggressive than that of pancreatic neuroendocrine neoplasms, and its prognosis is better. Limited surgery should be considered for cystic pancreatic endocrine neoplasms that are not accompanied preoperatively by lymph node or distant metastasis. Abstract : The biological behavior of a cystic pancreatic endocrine neoplasm is less aggressive than that of pancreatic neuroendocrine neoplasms, and its prognosis is better. Limited surgery should be considered for cystic pancreatic endocrine neoplasms that are not accompanied preoperatively by lymph node or distant metastasis.